2018
DOI: 10.7150/thno.27995
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-II (NIR-II) Bioimaging via Off-Peak NIR-I Fluorescence Emission

Abstract: Significantly reduced photon scattering and minimal tissue autofluorescence levels in the second biological transparency window (NIR-II; 1000-1700 nm) facilitate higher resolution in vivo biological imaging compared to tradition NIR fluorophores (~700-900 nm). However, the existing palette of NIR-II fluorescent agents including semiconducting inorganic nanomaterials and recently introduced small-molecule organic dyes face significant technical and regulatory hurdles prior to clinical translation. Fortunately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
182
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 79 publications
(100 reference statements)
4
182
0
Order By: Relevance
“…This finding highlights the possibility of using conventional NIR‐I dyes for NIR‐II imaging . Further imaging studies using commercially available NIR‐I dyes clearly demonstrate the success of this strategy, opening an entirely new route to realize NIR‐II imaging in preclinical research and even clinical imaging . However, this research direction is currently still in its infancy, and very few NIR‐I dyes have been identified with the capability for NIR‐II imaging.…”
Section: Introductionmentioning
confidence: 89%
“…This finding highlights the possibility of using conventional NIR‐I dyes for NIR‐II imaging . Further imaging studies using commercially available NIR‐I dyes clearly demonstrate the success of this strategy, opening an entirely new route to realize NIR‐II imaging in preclinical research and even clinical imaging . However, this research direction is currently still in its infancy, and very few NIR‐I dyes have been identified with the capability for NIR‐II imaging.…”
Section: Introductionmentioning
confidence: 89%
“…The recent introduction of near‐infrared tracers, such as ICG, permits real‐time transcutaneous and intraoperative visualization of lymphatic vessels and sentinel LNs. Currently, a huge number of clinical trials have showed that ICG method can be used as a reliable and safe alternative to the radiotracer method, which reduces operating time and potentially improve localization of the sentinel LNs . However, the ICG based clinically used contrast agents suffer from severe photobleaching, poor imaging detection depth, signal contrast, and sensitivity.…”
mentioning
confidence: 99%
“…Currently, a huge number of clinical trials have showed that ICG method can be used as a reliable and safe alternative to the radiotracer method, which reduces operating time and potentially improve localization of the sentinel LNs. [3][4][5][6][7] However, the ICG based clinically used contrast agents suffer from severe photobleaching, poor imaging detection depth, signal contrast, and sensitivity. Hence, current image-guided surgeries are performed under dim light or with frequent toggling of room light to avoid light interference and bleaching of dyes under repeated light exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion has focused in part on the relationship between the sp 2 -bonded regions in the dot’s core and the oxygen- and nitrogen-containing groups on its surface (Zheng et al 2015; Zhu et al 2018a, b; Ray et al 2009; Zhu et al 2012a, b; Wei et al 2014; Bourlinos et al 2008a, b; Li et al 2002; Kozák et al 2016). Some authors posit two separate mechanisms of emission (Baker and Baker 2010; Sun et al 2006; Li et al 2012a, b, c; Cao et al 2012a, b; Myung et al 2003; Zheng et al 2009).…”
Section: Carbon Dotsmentioning
confidence: 99%